A proposed mobile application for BPO night shift customer services representatives aimed for health promotion and assisting in managing the impact of returning to onsite work setup - Castelo, Karel Angelene A.
After 2 years of working remotely, night shift customer service representatives are now required to return to office. In addition to their reversed work schedule, which greatly affects their health, they are now faced with a significant change in their work environment.